Evaluasi Kualitas Website KPU Kabupaten Kediri Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Rony Kriswibowo; Budi Fajar Supriyanto; M. Habbibullah Arief; Jenike Gracelia Noke; Heni Vidia Sari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
The year 2020 is the year that the dependence with the use of the internet. Due to the pandemic Covid-19 all activities most use the Internet. Includes information on local elections (Elections) simultaneously. As the organizer of the KPU Kediri district also utilize the internet to the success of the dissemination of information and services through a media-based web site or website. Permasa-land in this study originated from the want to know how high people's satisfaction with website KPU Kediri district. People use the website to find information on Local Head Elections (PILKADA). The purpose of this study is to find out whether it is the achievement of services to the satisfaction of the public against the use of the website KPU Kediri district. This research method using Webqual 4.0 and Importance Performance Analysis (IPA). Sample this study uses purposive sampling technique with 100 respondents from the District. Kediri. The results of the research get the value of 93,5% with the value of the gap 0,226 it can be concluded that the level of service quality website KPU Kediri district has not been according to the expectations of society. The results of the Importance Performance Analysis (IPA) shows the mapping of the cartesian diagram is expected to improve the quality of information by providing the information up to date and that the in-formation given on the web site is still not in the appropriate format or still less precise arrangement of the informa-signal. So as to make respondent confusion. Researchers give advice for the management of the website management in preparing a strategy to improve the quality of website KPU Kediri.